PENGENALAN SCIENCE EXPERIMENT PEMBUATAN ICE CREAM KEPADA ANAK USIA DINI DI KABUPATEN SERANG BANTEN - Widyawati Widyawati (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2021)
Tinggar Village is one of the villages located in the Curug sub-district, where the area is located to the east of Serang City, Banten. One of the villages in the Tinggar village is Jengkol Village. In Jengkol Village there is a school named Raudhatul Athfal Bani Daud Al-Islami. Preschool which contains approximately 20 students. some students still have difficulties in accepting the learning process such as lack of courage in opinion and creativity, some students are still shy (lack of confidence), there are some students who are still experiencing problems in gross and fine motor development. Therefore, this service will carry out activities aimed at increasing students' self-confidence and motoric development. The activity was carried out on August 19, 2021at 10.00 WIB with a total of nine students. The implementation stages are the online preparation stage (google meet), the first conditioning stage, the preparation of the tools and materials needed, the implementation stage, and implementation review stage. The result is the implementation of activities to improve the development of students which can be seen from the implementation of activities, namely students are able to be more confident in expressing opinions and asking questions. Students can increase their knowledge about changing the shape of a liquid into a solid as a form of additional knowledge about science experiments. Furthermore, students can be trained how to express emotions by identifying and explaining the flavors produced from the ice cream or tasting raw materials such as knowing the taste of salt.